2010
DOI: 10.1111/j.1467-9922.2009.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching L2 Learners How to Listen Does Make a Difference: An Empirical Study

Abstract: This study investigated the effects of a metacognitive, process-based approach to teaching second language (L2) listening over a semester. Participants (N = 106) came from six intact sections of French as a second language (FSL) courses. The experimental group (n = 59) listened to texts using a methodology that led learners through the metacognitive processes (prediction/planning, monitoring, evaluating, and problem solving) underlying successful L2 listening. The control group (n = 47), taught by the same tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
420
5
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(483 citation statements)
references
References 64 publications
(108 reference statements)
47
420
5
11
Order By: Relevance
“…The results support the fact that if learners undergo such processes underlying the listening activity, they can surely benefit from this strategy, and metacognitive listening instruction does have merits in this regard. The present study found further empirical support to those of Goh (2002), Goh and Taib (2006), Vandergrift (2004), and Vandergrift and Tafaghodtari (2010), claiming that metaconitive listening instruction as a pedagogical cycle can improve learners' second and foreign language listening skills in the classroom if it is employed in a systematic way and based on the pedagogic needs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results support the fact that if learners undergo such processes underlying the listening activity, they can surely benefit from this strategy, and metacognitive listening instruction does have merits in this regard. The present study found further empirical support to those of Goh (2002), Goh and Taib (2006), Vandergrift (2004), and Vandergrift and Tafaghodtari (2010), claiming that metaconitive listening instruction as a pedagogical cycle can improve learners' second and foreign language listening skills in the classroom if it is employed in a systematic way and based on the pedagogic needs.…”
Section: Discussionsupporting
confidence: 61%
“…Before presenting the findings in terms of the treatment effectiveness for less-skilled listeners, it should be noted that based on the learners' mean on the pre-test (11.71) in the experimental group, it was assumed that those participants who received the grade of 12 or more than this value, were considered as more-skilled listeners while those learners whose listening grade was less than 12 were less-skilled learners (Vandergrift & Tafaghodtari, 2010). It is of value to note that the listening test (Cambridge Key English Test) consisted of 25 listening tests.…”
Section: Journal Of Education and Trainingmentioning
confidence: 99%
“…Listeners are to be provided with enough opportunities to act upon the set of rules already devised by the instructor. This regulated procedure helps listeners to plan, monitor, and evaluate their listening [5,6]. The pedagogical evidence from the study [7] shows that metacognitive instruction assists listeners in (i) what successful listeners choose to select for processing and (ii) improving successful language learning through acquiring metacognitive strategies.…”
Section: Metacognitive Instruction In Listeningmentioning
confidence: 99%
“…According to Vandergrift and Tafaghodtari (2010) there are distinct processes involve in listening comprehension. Listeners use "top down" processes when they use background knowledge to understand the meaning of a message.…”
Section: Theoretical Reviewmentioning
confidence: 99%